2005
DOI: 10.1016/j.neuroscience.2005.06.062
|View full text |Cite
|
Sign up to set email alerts
|

I.v. infusion of brain-derived neurotrophic factor gene-modified human mesenchymal stem cells protects against injury in a cerebral ischemia model in adult rat

Abstract: Abstract-I.v. delivery of mesenchymal stem cells prepared from adult bone marrow reduces infarction size and ameliorates functional deficits in rat cerebral ischemia models. Administration of the brain-derived neurotrophic factor to the infarction site has also been demonstrated to be neuroprotective. To test the hypothesis that brain-derived neurotrophic factor contributes to the therapeutic benefits of mesenchymal stem cell delivery, we compared the efficacy of systemic delivery of human mesenchymal stem cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
175
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(189 citation statements)
references
References 32 publications
(53 reference statements)
11
175
2
1
Order By: Relevance
“…Research activities focusing on NSC have shown that promoting their proliferation or grafting/infusing them by different routes into the brain leads to neurological improvement in different brain disease models, including stroke (Nomura et al, 2005;Pallini et al, 2005;Capone et al, 2007;Maysami et al, 2008). This benefit does not come only by their capacity to replace lost neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Research activities focusing on NSC have shown that promoting their proliferation or grafting/infusing them by different routes into the brain leads to neurological improvement in different brain disease models, including stroke (Nomura et al, 2005;Pallini et al, 2005;Capone et al, 2007;Maysami et al, 2008). This benefit does not come only by their capacity to replace lost neurons.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 Human MSCs were injected into rats after middle cerebral artery occlusion. 49,50 In both studies, implanted cells reduced the lesion volume and elicited functional improvement compared with the control sham group. As MSCs can be easily genetically modified, numerous studies in which MSCs overexpress some bioactive molecules have appeared.…”
Section: Stem Cells In Cnsmentioning
confidence: 96%
“…As MSCs can be easily genetically modified, numerous studies in which MSCs overexpress some bioactive molecules have appeared. [50][51][52] Human MSCs expressing brain-derived neurotrophic factor or human MSCs producing placental growth factor have an enhanced effect on functional outcome and lesion volume compared to human MSCs alone, suggesting the use of human MSCs as vehicles for the delivery of growth factors. As MSC-based treatments for brain disorders have advanced rapidly, the visualization of implanted stem cells in experimental models of brain disorders is at the leading edge of potential applications of MRI.…”
Section: Stem Cells In Cnsmentioning
confidence: 99%
“…Each rat was placed in an animal holder/MRI probe apparatus and positioned inside the magnet (Liu et al, 2006;Nomura et al, 2005). The animal's head was held in place inside the RF coil.…”
Section: Mrimentioning
confidence: 99%